‘Greening’ the UK: a comparative study of heat pumps and hydrogen boilers in residential heating - Gao, Lin; Naylor, Philip; Hegab, Abdelrahman; Pilidis, Pericles (MDPI, 2026)
With a key policy decision on the role of hydrogen boilers expected by 2026, the UK is at a strategic crossroads in implementing its Heat and Buildings Strategy. This study evaluates the relative advantages of hydrogen boilers and heat pumps in residential heating, focusing on their impact on national energy demand, which is a critical factor in achieving full decarbonisation by 2050. Using the End-state Decarbonisation Resource Analysis framework, this study demonstrates that electrification with widespread heat pumps could reduce current residential primary energy demand by over 53%, whereas a hydrogen boiler-dominant pathway could increase demand by 42%. When translated into generation and infrastructure requirements, the hydrogen pathway would demand significantly more resources than the heat pump alternative. Incorporating heat pumps into the electrification strategy would make the delivery of net-zero targets more achievable. Notably, heat pumps could deliver nearly six times higher economic benefits than hydrogen, while requiring only 67% of investment needed for additional generation assets. These findings support prioritising heat pumps over hydrogen boilers in the UK’s national residential decarbonisation strategy.
This article belongs to the Special Issue Energy Transition: Interaction of Gas/Hydrogen and Electricity Systems
Keywords: 40 Engineering; 33 Built environment and design; 51 Physical sciences; decarbonisation; hydrogen; natural gas; heat pump; renewables; nuclear; electricity; energy system; energy policy; energy investment